Regional assessment of exposure to traffic-related air pollution: Impacts of individual mobility and transit investment scenarios. (February 2017) - Shekarrizfard, Maryam; Faghih-Imani, Ahmadreza; Tétreault, Louis-Francois; Yasmin, Shamsunnahar; Reynaud, Frederic; Morency, Patrick; Plante, Celine; Drouin, Louis; Smargiassi, Audrey; Eluru, Naveen; Hatzopoulou, Marianne
Highlights: Integrated model evaluated impacts of transit and vehicle improvements on exposure. We observed an increase in modal share of public transit and lower traffic volumes. We observed lower emissions and NO2 concentrations in the downtown area. The effect of transit policy on exposure is smaller than vehicle technology. Abstract: This paper describes the design and application of an integrated model for the prediction of exposure to traffic related air pollution in an urban area as a result of transport policy scenarios. For this purpose, a travel demand model linked with models for traffic assignment, emissions, and air quality was used to simulate population exposure to ambient Nitrogen Dioxide (NO2 ) in a base year (2008) and in a horizon year (2031) while incorporating population and demographic projections. The integrated model was used to evaluate the impacts of the planned regional transit and vehicle technology improvements on exposure to NO2 . In the 2031 business as usual scenario, an average decrease of 19% in exposure to NO2 is observed across the sample population, compared to the 2008 base case. This decrease is primarily attributed to projected improvements in vehicle technology. In the 2031 transit scenario, we observed an average 10% decrease in exposure compared to the 2031 business as usual. In terms of the spatial variability in air pollution, the transit scenario was observed to achieve large reductions in NO2 concentrations within the downtown area and moderate reductions throughout the suburbs.